The Effect Of Profitability and Corporate Social Responsibility Disclosures on Company Value - Anak Agung Putri Winasari; Putu Ery Setiawan (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Company value is a condition achieved by a company which is a reflection of public trust in the company. For companies going public, the company's value is reflected through its share price. Profitability is one of the financial factors that will be able to show the company's ability to achieve profits. Disclosure of corporate social responsibility is a non-financial factor as a form of corporate responsibility for the social and environmental impacts of the economic activities it causes. The aim of this research is to determine the effect of profitability and corporate social responsibility disclosure on the value of non-financial sector companies for the 2020-2022 period. This research uses the Compass 100 index, which is a stock index that measures the price performance of 100 stocks that have good liquidity and large market capitalization. The population was selected using a purposive sampling technique because not all companies in the research population met the specified criteria. The research results show that profitability and disclosure of corporate social responsibility have a positive effect on company value.